Mojito, Anyone? An Exploration of Low-Tech Plant Water Extraction Methods for Isotopic Analysis Using Locally-Sourced Materials - Fischer, Benjamin M. C.; Frentress, Jay; Manzoni, Stefano; Cousins, Sara A. O.; Hugelius, Gustaf; Greger, Maria; Smittenberg, Rienk H.; Lyon, Steve W. (Frontiers in Earth Science, 2019)
The stable water isotopic composition of water (18O and 2H) is an increasingly utilized tool to distinguish between different pools of water along the soil‐plant‐atmosphere continuum (SPAC) and thus inform on how plants use water. Clear bottlenecks for the ubiquitous application of isotopic analysis across the SPAC are the relatively high-energy and specialized materials required to extract water from plant materials. Could simple and cost-effective do-it-yourself “MacGyver” methods be sufficient for extracting plant water for isotopic analysis? This study develops a suite of novel techniques for plant water extraction and compares them to a standard research-grade water extraction method. Our results show that low-tech methods using locally-sourced materials can indeed extract plant water consistently and comparably to what is done with other state-of-the-art methods. Further, our findings show that other factors play a larger role than water extraction methods in achieving the desired accuracy and precision of stable isotope composition: (1) appropriate transport, (2) fast sample processing and (3) efficient workflows. These results are methodologically promising for the rapid expansion of isotopic investigations, especially for citizen science and/or school projects or in remote areas, where improved SPAC understanding could help manage water resources to fulfill agricultural and other competing water needs.